دور االستقامة التنظيمية في تحسين جودة حياة العمل )دراسة تحليلية ألراء عينة من العاملين في كليات جامعة صالح الدين في مدينة أربيل( - القرداغي, كاوه محمد فرج; حسين, رازاو عبدالخالق (Sulaimani Journal for Humanities, 2022)
The aim of the research is to identify the role Organizational Integrity with its subdivisions (Optimism, Trust, Forgiveness) in Quality of Work Life. The research presented theoretical and conceptual framework for the main and secondary variables. employes at the Colleges of SalahaddinUniversity and number of its directorates were chosen as a field for conducting the research. The importance of the research stems from the importance of the topics examined. The research was systematically and descriptively analyzed, and a set of hypotheses was identified as probative responses to the research problem, which were tested using multiple statistical tools, using the SPSS-V.20 statistical program. The questionnaire was used as a means of obtaining the data. It was distributed to a sample of employes of Salahaddin University The number of employe was 65, and 63 questionnaires were retrieved and all were valid for analysis. The study concluded that there is a relationship and influence for all dimensions of Organizational Integrity in Quality of Work Life. The research recommended employing this relationship to serve the employe of Colleges SalahaddinUniversity.
Keywords: Organizational Integrity; Optimism; Trust; Forgiveness; Quality of Work Life